2021
DOI: 10.2174/1871520620666200721131431
|View full text |Cite
|
Sign up to set email alerts
|

Thieno[2,3-d]pyrimidin-4(3H)-one Derivatives of Benzimidazole as Potential Anti- Breast Cancer (MDA-MB-231, MCF-7) Agents

Abstract: Aims: The purpose was the synthesis of some new thienopyrimidines derivative of 1,3-disubstituted benzimidazoles and the evaluation of their cytotoxicity towards MDA-MB-231 and MCF-7 cell lines as well 3T3 cells. Background: An overexpression or mutational activation of TK receptors EGFR and HER2/neu are characteristic for tumors. It has been found that some thieno[2,3-d]pyrimidines exhibit better inhibitory activity against epidermal growth factor receptor (EGFR/ErbB-2) tyrosine kinase in comparison to ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…[70,71] In this trend, various thieno [2,3d]pyrimidine-based-N,N-disubstituted-benzimidazole derivatives were synthesized to estimate their cytotoxicity proficiency against MDA-MB-231 and MCF-7 cell lines. [72] The results show that almost all the benzimidazoles demonstrated a short range of activity towards MDA-MB-231, MCF-7, and fibroblast 3T3 cells. In contrast, some displayed comparatively proper viability against MCF-7 and 3T3 cell lines.…”
Section: Kinase Inhibitorsmentioning
confidence: 92%
See 1 more Smart Citation
“…[70,71] In this trend, various thieno [2,3d]pyrimidine-based-N,N-disubstituted-benzimidazole derivatives were synthesized to estimate their cytotoxicity proficiency against MDA-MB-231 and MCF-7 cell lines. [72] The results show that almost all the benzimidazoles demonstrated a short range of activity towards MDA-MB-231, MCF-7, and fibroblast 3T3 cells. In contrast, some displayed comparatively proper viability against MCF-7 and 3T3 cell lines.…”
Section: Kinase Inhibitorsmentioning
confidence: 92%
“…According to scientific explorations, mutations can influence EGFR (or other receptor tyrosine kinases) expression, thereby leading to over‐expression which is responsible for different categories of cancer [70,71] . In this trend, various thieno[2,3‐d]pyrimidine‐based‐ N , N ‐disubstituted‐benzimidazole derivatives were synthesized to estimate their cytotoxicity proficiency against MDA‐MB‐231 and MCF‐7 cell lines [72] . The results show that almost all the benzimidazoles demonstrated a short range of activity towards MDA‐MB‐231, MCF‐7, and fibroblast 3T3 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H ‐benzimidazole‐2‐one‐thieno[2,3‐ d ]pyrimidin‐4(3 H )‐one hybrid 49 (IC 50 : 29.0 and 74.0 nM, MTT assay) exhibited pronounced activity against MCF‐7 and MDA‐MB‐231 breast cancer cell lines, demonstrating its potential as a novel antibreast cancer candidate. [ 105,106 ]…”
Section: Benzimidazole‐pyrimidine Hybridsmentioning
confidence: 99%
“…[104] The mechanistic study revealed that hybrid 48 and MDA-MB-231 breast cancer cell lines, demonstrating its potential as a novel antibreast cancer candidate. [105,106]…”
Section: Benzimidazole-cinnamic Acid Hybridsmentioning
confidence: 99%
“…As the discussed PTKs are therapeutical targets in cancer treatment, and on the basis of the above-mentioned thienopyrimidines’ inhibitory properties, we set ourselves the objective to design and synthesize 4-amino-thieno [2,3-d]pyrimidines in order to study both their activity against human cancer cell lines and their effects on normal cell lines. This investigation is a continuation of our foregoing study of the cytotoxicity effects of thienopyrimidines on human cancer cell lines (MDA-MB-231, MCF-7, HT-29, HeLa, HepG2) as well as towards normal human cells [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%